Effect of organic cultivation of Picual and Hojiblanca olive varieties on the quality of virgin olive oil at four ripening stages. Issue 12 (1st August 2014) - Jimenez, Brigida; Sánchez‐Ortiz, Araceli; Lorenzo, Maria Luisa; Rivas, Ana
<x xml:space="preserve">Abstract</x> In recent years, there has been a remarkable development of organic agriculture worldwide, including in olive cultivation. The objective of this study was to evaluate the physicochemical characteristics and nutritional quality of virgin olive oils extracted from two of the most widespread olive varieties in Spain (Picual and Hojiblanca) at different olive‐ripening stages, grown using organic or conventional methods. The results of this study showed significant differences in the acidity, oxidative stability, tocopherol contents, fatty acid composition and phenol contents of oils from organically and conventionally cultivated olives. However, the variety and the maturity stage of the olives had a greater effect on the physico‐chemical and nutritional parameters than whether the cultivation method was organic or conventional. Due to the growing interest in organic olive oil in the national and international markets, more studies that analyse the effect of organic cultivation on the quality of olive oil are required. <inline-graphic xlink:href="ark:/27927/pgh2qxdb8hr" content-type="ejlt201400010-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> This study evaluates the quality characteristics of virgin olive oils extracted from two of the most widespread olive varieties in Spain (Picual and Hojiblanca) at different olive‐ripening stages, grown using organic or conventional methods. The results showed significant differences in the acidity, oxidative stability, tocopherol contents, fatty acid composition and phenol contents of oils from organically and conventionally cultivated olives.